Marimbondos: systematics, biogeography, and evolution of social behaviour of neotropical swarm-founding wasps (Hymenoptera: Vespidae: Epiponini) - Noll, Fernando B. [UNESP]; da Silva, Marjorie [UNESP]; Soleman, Raduan A. [UNESP]; Lopes, Rogério B. [UNESP]; Grandinete, Yuri C. [UNESP]; Almeida, Eduardo A. B.; Wenzel, John W.; Carpenter, James M. (Wiley, 2020)
Neotropical swarm-founding wasps are divided into 19 genera in the tribe Epiponini (Vespidae, Polistinae). They display extensive variation in several colony-level traits that make them an attractive model system for reconstructing the evolution of social phenotypes, including caste dimorphism and nest architecture. Epiponini has been upheld as a solid monophyletic group in most phylogenetic analyses carried out so far, supported by molecular, morphological and behavioural data. Recent molecular studies, however, propose different relationships among the genera of swarm-founding wasps. This study is based on the most comprehensive epiponine sampling so far and was analyzed by combining morphological, nesting and molecular data. The resulting phylogenetic hypothesis shows many of the traditional clades but still impacts the way certain behavioural characters, such as nest structure and castes, evolved, and thus requires some re-interpretations. Angiopolybia as sister to the remaining Epiponini implies that nest envelopes and a casteless system are plesiomorphic in the tribe. Molecular dating points to an early tribal diversification during the Eocene (c. 55–38 Ma), with the major differentiation of current genera concentrated in the Oligocene/Miocene boundary.